On limits of induced radiation concept in FELs - Gorbunov, M.A.; Lebedev, A.N. (Вопросы атомной науки и техники, 2008)
We discuss a restriction of the induced radiation concept in classical beam systems due to accompanying spontaneous radiation (radiation friction). For short wave-length FELs spontaneous radiation renders a noticeable influence on phasing of particles which is the base mechanism of induced radiation in classical systems. It leads to an essential restriction on the radiating system length and gain which cannot be compensated by an increase in the beam current. Розглянуто обмеження концепції індукованого випромінювання в класичних пучкових системах, зв’язане з обліком супутнього спонтанного випромінювання (радіаційного тертя). Показано, що при укороченні довжини хвилі в ЛВЕ спонтанне випромінювання впливає на фазування частинок. Це приводить до практично важливого обмеження на довжину випромінюючої системи, що не може бути скомпенсовано збільшенням струму пучка. Рассмотрено ограничение концепции индуцированного излучения в классических пучковых системах, связанное с учётом сопутствующего спонтанного излучения (радиационного трения). Показано, что при укорочении длины волны в ЛСЭ спонтанное излучение оказывает существенное влияние на фазировку частиц. Это приводит к практически важному ограничению на длину излучающей системы, которое не может быть скомпенсировано увеличением тока пучка.